Defisiensi Vitamin D dan Benign Paroxysmal Positional Vertigo Rekuren - Deva J. Karel; Olivia C. P. Pelealu; Rizki R. Najoan (Medical Scope Journal, 2023)
Abstract: Benign paroxysmal positional vertigo (BPPV) is the most common peripheral vestibular disturbance. Recurrency of BPPV is highly reported in females and elderly group. This study aimed to evaluate the association between vitamin D deficiency and recurrent BPPV events. This was a literature review study using PubMed, ClinicalKey, and GoogleScholar databases. The results obtained 13 literatures according to the predetermined inclusion and exclusion criteria. Vitamin D deficiency caused disturbances in calcium metabolism and degradation of otoconia. Release of otoconia debris into the endolymph fluid could trigger the BPPV attack. Based on demography, recurrent BPPV was most frequent among female elderlies with osteoporosis/osteopenia. The level of 25(OH)D of recurrent BPPV group was lower than the non-recurrent BPPV group, and supplementation of vitamin D could reduce the recurrency of BPPV. In conclusion, vitamin D deficiency is one of the causes of recurrent BPPV since it affects the metabolism of calcium which is the constituent component of otoconia. Instability of otoconia will affect the release of otoconia debris into the endolymph fluid triggering the BPPV attacks and increasing the risk of recurrent BPPV. Vitamin D supplementation can reduce the BPPV recurrence level. Keywords: recurrent benign paroxysmal positional vertigo; vitamin D deficiency; calcium metabolism; female; elderly   Abstrak: Benign paroxysmal positional vertigo (BPPV) merupakan penyakit gangguan keseimbangan perifer yang paling sering ditemui. Rekurensi BPPV dilaporkan lebih tinggi pada kelompok wanita dan usia lanjut. Penelitian ini bertujuan untuk mengetahui hubungan antara defisiensi vitamin D dan kejadian BPPV rekuren. Jenis penelitian ialah literature review menggunakan database PubMed, ClinicalKey, dan Google Scholar. Hasil penelitian mendapatkan 13 literatur yang ditelaah berdasarkan kriteria inklusi dan eksklusi yang ditetapkan. Pada defisiensi vitamin D terjadi gangguan metabolisme kalsium dan degradasi otokonia. Debris otokonia yang terlepas ke dalam cairan endolimf dapat memicu terjadinya serangan BPPV. Secara demografi, BPPV rekuren lebih sering dijumpai pada perempuan usia lanjut dan memiliki riwayat osteoporosis/ osteopenia. Kadar 25(OH)D pada kelompok BPPV rekuren lebih rendah dibandingkan dengan kadar 25(OH)D pada kelompok non-BPPV rekuren, dan pemberian suplementasi vitamin D dapat menurunkan tingkat rekurensi pasien BPPV. Simpulan penelitian ini ialah defisiensi vitamin D merupakan salah satu penyebab dari perjalanan penyakit BPPV menjadi rekuren. Defisiensi vitamin ini memengaruhi metabolisme kalsium yang merupakan komponen penyusun otokonia. Instabilitas otokonia akan memengaruhi pelepasan debris ke cairan endolimf sehingga mencetuskan serangan BPPV dan meningkatkan risiko terjadinya BPPV rekuren. Pemberian suplementasi vitamin D dapat menurunkan tingkat rekurensi BPPV. Kata kunci: benign paroxysmal positional vertigo rekuren, defisiensi vitamin D; metabolism kalsium; jenis kelamin perempuan; usia lanjut